Empire of the summer moon [compact disc, unabridged] : Quanah Parker and the rise and fall of the Comanches, the most powerful Indian tribe in American history - Gwynne, S. C. (Samuel C.), 1953- (Tantor Audio, 2010)
A history of the 40-year battle between the Comanche Indians and white settlers, centering on the Comanche chief Quanah.